Sugarcane root and shoot phytomass related to nitrogen fertilization at planting - Otto, Rafael; Franco, Henrique Coutinho Junqueira; Faroni, Carlos Eduardo; Vitti, André César; Trivelin, Paulo César Ocheuze (Pesquisa Agropecuaria Brasileira, 2010)
This work evaluated the root and shoot sugarcane (Saccharum spp.) development in plant cane cycle, related to nitrogen (N) rates applied at planting. Two experiments were carried out using randomized block designs, one in a Typic Eutrustox and other in an Arenic Kandiustults. Treatments were a control without N, and 40, 80 and 120 kg ha-1 N applied in furrow at planting, with four replicates. The root and shoot masses were evaluated in three periods (October 2005, February 2006 and June/July 2006). Shoots were collected in 2 m of furrow, and the roots were collected using a probe (internal diameter of 0.055 m) until 0.6 m depth. The nitrogen fertilization at planting increased the development of cane roots and shoots in Typic Eutrustox. However, there was no growth increase of sugarcane roots and shoots in the Arenic Kandiustults where a large amount of organic N from cultural residues had been incorporated into the soil. The phase of larger root development of one and half year old plant cane was from October to February, with decrease of the root mass from February to July.